Vitimização secundária: o depoimento especial como instrumento de concretização da proteção integral de crianças e adolescentes submetidos a abuso sexual - Iulianello, Annunziata Alves (2018)
The process of revictimization of children and tennagers subjected to sexual abuse that occurred before the formal instances of social control, known as secondary victimization, is something that demands special attention. The victim, throughout history, in criminal and criminal procedural science, has migrated from the leading role to the forgotten figure. More recently, however, there has been a growing concern for victims of crime, with legislative reforms in the criminal procedural sphere allowing for more effective measures to be taken to protect victims' rights. In this scenario, taking into account the need for protection of the most vulnerable victims, Law 13.431 / 17 established the system of guaranteeing the rights of child and adolescent victims or witnesses of violence, expressly inserting in the Brazilian legal system the special testimony, an important tool to prevent the revictimization of children and adolescents - especially those who have been sexually abused - before the justice system. Thus, the scope of the present work consists precisely in making an analysis about the fundamental role that the special testimony has in order to avoid not only revictimization, to make it possible to obtain the declarations of the minor victim as reliable as possible, avoiding the formation of false memories, thus enabling the best reproduction of the facts in court. This is a compilation work, in which the methodology of qualitative nature was used through the technique of document analysis, such as books and specialized articles, legislation and jurisprudence. It is sought, from an interdisciplinary analysis, especially with the use of concepts brought by Victimology and Psychology, to expose the importance of the differentiated form that should be used in the criminal prosecution in the hypothesis of extreme vulnerability, as the cases that involve sexual abuse of children and adolescents. Only in this way can it be possible to talk about the realization of integral protection, avoiding the deficient protection of legal good. It is concluded, therefore, that the special testimony is a cogent provision, and all the professionals who work in the network for the protection of children and youth in the justice system should make efforts to make it a reality